Inelasticity distributions in high-energy p-nucleus collisions - Hama, Yogiro; Paiva, Samya [UNESP] (American Physical Society (APS), 1997)
Inelasticity distributions in high-energy p-nucleus collisions are computed in the framework of the interacting gluon model, with the impact-parameter fluctuation included. A proper account of the peripheral events by this fluctuation has shown to be vital for the overall agreement with several reported data. The energy dependence is found to be weak.